STRUKTURA PARCIJALIZOVANOG MOTORIČKOG PROSTORA UČENIKA ADOLESCENTNE DOBI - Kemal Idrizović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Knowing the hierarchical structure of the factors that determine the results in individual sports disciplines, and in whose specification equations sprint speed and explosive power play a dominant role, makes the basic assumption of rational implementation of procedures of selection and classification of potential competitors in these events, and more efficient planning, programming and training process control. Therefore, the practice of sport is increasingly interested in scientific research that can provide the most useful information on the structure and relations between certain segments of the psychosomatic status of a man and results performance in some sports activities. Period in motor development between the phenomena of differentiation and amalgamation is certainly one of the most interesting in ontogenesis in general. As it is largely coincided with nearly complete length of the period of adolescence, the need for monitoring individual motor segments and their structure becomes evident.